Upping the antedrug: is a novel anti-inflammatory Toll-like receptor 7 agonist also a bronchodilator? - Kaufman, EH (Blackwell Publishing Ltd, 2012)
In this issue of British Journal of Pharmacology, Biffen and colleagues present a novel Toll-like receptor 7 (TLR7) antedrug to treat allergic disease that is rapidly metabolized in the lung to limit side effects due to systemic exposure. Asthma is characterized as an allergic disease of the lung, and TLR7 agonists are proposed to ameliorate allergic inflammation in the lung, a characteristic of prophylactic medications. We have previously shown that TLR7 agonists of multiple structural classes are acute bronchodilators, characteristic of rescue medication for asthma attacks. It will be interesting to determine whether the bronchodilating effect extends to the novel class of TLR7 agonists described here for a prophylactic and rescue therapy in one drug. Combined with the antedrug approach, this would further limit side effects improving on current combination therapies. LINKED ARTICLE: This article is a commentary on Biffen et al., pp. 573–586 of this issue. To view this paper visit http://dx.doi.org/10.1111/j.1476-5381.2011.01790.x